Corporate Crime Legislation: A Political Economy Analysis - Vikramaditya S. Khanna (Washington University Law Quarterly, 2004)
Corporate crime has once again become an important issue on the U.S. legislative agenda, leading Congress and the various regulatory bodies to tighten the law and enhance honesty and completeness in disclosure. However, the continued and rather explosive growth of corporate crime legislation leaves one with a rather strange puzzle: how can such a state of the world arise? After all, corporations and business interests are considered some of the most, if not the most, powerful and effective lobbyists in the country. Yet, we witness the continued expansion of legislation that criminalizes their behavior (one estimate suggests over 300,000 federal regulatory offenses that can be prosecuted criminally). How could this have happened? This Article sets out to explain this puzzle. Overall, my analysis suggests that most corporate crime legislation arises when there is a large public outcry over a series of corporate scandals during or around a downturn in the economy. In such situations, Congress must respond. Corporate crime legislation may be the preferred response for some corporate interests because it satisfies public outcry while imposing relatively low costs on those interests, thereby avoiding legislative and judicial responses that are more harmful to their interests and sometimes deflecting criminal liability away from managers and executives and onto corporations. This explains not only the impressive growth of corporate crime legislation but also leads to some surprising normative conclusions. In particular, it suggests that if one starts with the view that there is under-deterrence of corporate wrongdoing, then one would probably prefer to reduce corporate criminal liability and focus more on corporate civil and managerial liability.
Keywords: Criminal liability of juristic persons; Economic history; Prosecution -- Decision making; Corporate corruption